(untitled) (Agricultural Engineering, 2022)
The purpose of the study was to use reverse engineering to model biological products, especially sugar beet root. In the process of creating the solid model, the appropriate tools available in the 3D design environment were applied. The 3D scan of the beet, in the form of a spatial point cloud, was used to project the root geometry. This was, in turn, used to construct a triangulation grid that includes nodal points of triangles. The subsequent steps presented the process of creating a solid model using the Interpolation Spline tool. Attention has been paid to the possibility of modifying the geometry by inserting additional points into the existing interpolation spline and changing angular position as well as the distance of the structural planes. Geometry mapping error values were determined with regard to the reference model depending on the spread value of the Structural Planes. Error courses are non-linear with a logarithmic line trend (surface field error) and a linear line trend (volume error). The effects demonstrated the usefulness of geometry projection and its applicability to support the strength testing of biological materials, with particular emphasis on dynamic tests using whole roots.